Complexin suppresses spontaneous exocytosis by capturing the membrane-proximal regions of VAMP2 and SNAP25 - Malsam, Jörg; Bärfuss, Simon; Trimbuch, Thorsten; Zarebidaki, Fereshteh; Sonnen, Andreas F. -P.; Wild, Klemens; Malsam, Andrea; Rohland, Lukas; Mayer, Matthias P.; Sinning, Irmgard; Briggs, John A. G.; Rosenmund, Christian; et al. (Cell reports, 2020)
The neuronal protein complexin contains multiple domains that exert clamping and facilitatory functions to tune spontaneous and action potential-triggered synaptic release. We address the clamping mechanism and show that the accessory helix of complexin arrests assembly of the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex that forms the core machinery of intracellular membrane fusion. In a reconstituted fusion assay, site- and stage-specific photo-cross-linking reveals that, prior to fusion, the complexin accessory helix laterally binds the membrane-proximal C-terminal ends of SNAP25 and VAMP2. Corresponding complexin interface mutants selectively increase spontaneous release of neurotransmitters in living neurons, implying that the accessory helix suppresses final zippering/assembly of the SNARE four-helix bundle by restraining VAMP2 and SNAP25.
Gesehen am 26.10.2020